Major reasons behind the whitewash of lakshmi vilas bank from the indian stock market – an analysis with mathematical approach - M, Vivek Prabu; K S, Dharani (Kongunadu Research Journal, 2021)
Banks play a pivotal role in India's economic development. They sustain the country’s GDP growth through turning people’s static money into capital for investment and thus directing cash flow via dynamic market systems. Bank deposits provide secured and fixed return unlike the share market that holds higher risk of investment and offer a variable return which is uncertain. Whenever an individual or a company is at financial crisis, Banks lend their hands and offer loans and help them as much as possible to cut down the financial burden. But on the other hand, when the financial health of a bank itself is very weak which in turn will certainly affect the entire movement of the banking sector in the stock market and further that would lead to unreliable market circumstances. In this paper, we will be analyzing the major reasons behind the complete wash out of Lakshmi Vilas Bank from the Indian Stock Market and try to figure out the alarming indicators so as to be more cautious in the mere future to avoid such financial breakdown caused due to the bankrupted scenario.